Centralized Authentication Smart Locking System using RFID, Fingerprint, Password and GSM - Sai Divya, M; Nagabhushana Rao, M (International Journal of Engineering and Technology, 2018)
The primary aim of implemented project is design of the RFID based high security building locking system, fingerprint, GSM technology, and password. In the implemented system, only authorized person can be enter from the building door locking by scanning his card. The implemented building locking system works based on the RFID, Password, GSM and Fingerprint. The Door locking system can be activated for authorized and valid user by scanning his card and unauthorized user enters in the building a Gsm module sent a message to authority unauthorized user entering in the building.Â Â